Previous Trauma Exposure and Its Associations with Fear of Childbirth and Quality of Life among Pregnant Lesbian, Bisexual, Transgender, and Queer People and Their Partners. Issue 2 (15th March 2023) - Grundström, Hanna; Malmquist, Anna; Karlsson, Amanda; Nieminen, Katri
Abstract: The primary aim of this study was to determine the prevalence of previous trauma exposure among expectant birth-giving parents and their partners within a LBTQ population. The secondary aims were to compare fear of childbirth (FOC) and quality of life (QoL) in relation to previous trauma exposure in pregnant LBTQ people and their partners. A further aim was to analyze associations between severe FOC and clinical and demographic factors in this population. Data was collected from a Swedish LGBTQ competent antenatal clinic. Trauma-exposed pregnant (n = 32) and non-pregnant (n = 21) individuals and pregnant (n = 48) and non-pregnant (n = 30) individuals without previous trauma experiences responded to instruments measuring FOC (Wijma Delivery Expectancy Questionnaire) and QoL (EuroQol 5 D-index/-visual analogue scale, VAS). Differences between groups were assessed using non-parametric tests. The proportion of trauma exposure was similar among pregnant responders and their partners (40.0% vs. 41.2%). Trauma-exposed pregnant respondents had a significantly higher prevalence of severe FOC compared to the pregnant respondents without previous trauma. Pregnant trauma-exposed respondents scored lower on EQ5D-VAS than pregnant respondents without trauma, as did non-pregnant trauma exposed respondents compared with non-pregnant respondents without trauma. Furthermore, trauma-exposed non-pregnant respondents scored lower on the EQ5D-index compared to non-pregnant respondents without trauma. Previous trauma was the only clinical and demographic factor that had any significant association withto severe FOC in the regression analysis. In conclusion, our results suggest that previous trauma exposure may contribute to the risk of suffering from severe FOC and lower QoL among LBTQ-identifying prospective parents.